2020
DOI: 10.2306/scienceasia1513-1874.2020.091
|View full text |Cite
|
Sign up to set email alerts
|

Suspended microplastics during a tidal cycle in sea-surface waters around Chao Phraya River mouth, Thailand

Abstract: The study investigated the influence of tides (low and high) on composition and abundance of microplastic. Suspended microplastics (MP) were sampled in surface waters around the Chaophraya River mouth in Upper Gulf of Thailand using Neuston trawl (330-µm mesh) during tidal cycle at both tides in rainy season (August) of 2019. The abundance and types of microplastic had been analyzed. Overall, the concentration of MP during spring tide was significantly lower than the concentration during neap tide (p < 0.01). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Inconsistent results were identified in these studies concerning the impacts of spring/neap tide and flood/ebb tide on the MP concentration in the water or sediment phase. For instance, Sukhsangchan et al reported neap tide to have a greater abundance of MPs compared to spring tide in surface water near a river mouth, whereas Sadri and Thompson found that more MPs were observed in the surface water during spring tides. Wu et al found MPs to be more abundant in the surface sediment layer in the neap tide compared to in the spring tide, where the concentration of MPs exhibited a negative correlation with hydrological forces in an estuary.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistent results were identified in these studies concerning the impacts of spring/neap tide and flood/ebb tide on the MP concentration in the water or sediment phase. For instance, Sukhsangchan et al reported neap tide to have a greater abundance of MPs compared to spring tide in surface water near a river mouth, whereas Sadri and Thompson found that more MPs were observed in the surface water during spring tides. Wu et al found MPs to be more abundant in the surface sediment layer in the neap tide compared to in the spring tide, where the concentration of MPs exhibited a negative correlation with hydrological forces in an estuary.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, several studies on microplastics in marine ecosystem have been conducted in Thailand, with the focus on marine organisms [34,35], estuarine environments [36,37], and ocean sediment [38]. Despite this, the accumulation of ingested microplastics in fish has been less emphasized [39].…”
Section: Introductionmentioning
confidence: 99%
“…Tidal current velocity was found to vary greatly for different sites and changes between neap and spring tides. For instance, some previous studies reported that tidal velocities ranged between 0.01 to approximately 1 m/s. This can be expected to lead to different rates of change to the water table. Figure d–f demonstrates the effects of water table fluctuation velocity on MP movement in the substrate.…”
Section: Resultsmentioning
confidence: 99%